Two-dimension, high spatial resolution detector of thermal and subthermal neutrons based on ccd and cmos electronics sensors, and converter containning gadolinium - Alcalde Bessia, Fabricio; Berisso, Mariano; Blostein, Juan Jerónimo; Lipovetzky, José; Pastoriza, Hernán; Pérez, Martín; Sidelnik, Iván Pedro; Sofo Haro, Miguel; Tartaglione, Aureliano (2017)
Fil: Alcalde Bessia, Fabricio. Comisión Nacional de Energía Atómica; Argentina.